Parents’ Feelings, Coping Strategies and Sense of Parental Self-Efficacy When Dealing With Children’s Victimization Experiences - Benatov, Joy (Frontiers in Psychiatry, 2019)
Background: Accumulating evidence strongly suggests that bullying victimization poses a major risk for children's and adolescents' socio-emotional development. Despite the key role parents play in their child's ability to cope with bullying, very few studies have focused on parents' reactions to their children's victimization. The current study examined parents' feelings, coping strategies and sense of parental self-efficacy subsequent to their children's victimization. Methods: The sample was composed of 217 parents of children aged 7 to18 who had been victims of bullying. Parents were requested to fill in a self-report survey measuring their responses to their child's bullying victimization in the last 12 months, the feelings they experienced the coping strategies they implemented and their sense of parental self-efficacy in dealing with the situation. Results: Parents of victimized children experienced notable emotional distress and an array of complex emotions. A unique pattern of associations was revealed between feelings and coping tactics. Specifically, feelings of guilt were predictive of parents adopting avoidance and self-blame strategies and negatively associated with providing support to the child. Parent's feelings of sadness positively predicted coping by providing child support and negatively linked to avoidance coping. Anger was predictive of retaliative coping, whereas worry contributed to child restrictions. Providing support to the child and retaliation positively contributed to parental self-efficacy in dealing with the victimization events, whereas seeking social support was negatively associated with parents' sense of efficacy. Discussion: It is suggested that bullying prevention efforts should include parents, and address the complex feelings they experience, especially feelings of guilt and anger which were found to contribute to a maladaptive coping reaction.